Speech rehabilitation of cleft palate cases with superiorly projected dome prosthesis and intensive speech therapy - Oza RK; Chitre AS; Hiranandani H; Mirza FD (Journal of All India Institute of Speech and Hearing, 1970)
Plastic surgery of cleft palate cases has made a remarkable advance and many cases benefit from it. For many unknown factors, in spite of this advance in plastic surgery, there are several cases which do not acquire proper functional closure of the nasopharynx and the result is nasal speech with poor articulation and intelligibility.  It is, therefore, necessary to evolve some other useful method of achieving the velopharyngeal closure. In this paper, we have dealt at length with the usefulness of a 'custom-made' prosthetic device.